Makna Simbolik Proses Ritual Suku Bajo dalam Aktivitas Melaut di Desa Parumaan Kecamatan Alok Timur Kabupaten Sikka - Karim Karim; Gisela Nuwa; Abbdullah Muis Kasim (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2024)
This research uses a qualitative research approach, the main goal of this research is to explain the symbolic meaning of the fishing ritual (equ) carried out by Bajo tribe in Parumaan Village, East Alok District, Sikka Regency. In-depth interviews, documentation, and observation methods are some of the data collection strategies used. Research findings showed that the Bajo tribes carried out a number of ceremonial processes related to fish arrest activities, including rituals before fish arrest, during fish arrest, and after fish arrest. Each ritual procedure has a symbolic meaning that is closely related to customs, beliefs, local people. This symbolic meaning includes showing respect to the Creator, requesting refuge, asking for the results of an abundant catch, and preserving.